Western boundary current in relation to Atlantic Subtropical Gyre dynamics during abrupt glacial climate fluctuations - Nürnberg, Dirk; Riff, Tabitha; Bahr, André; Karas, Cyrus; Meier, Karl J. F.; Lippold, Jörg (Global and planetary change, 2021)
Ocean-atmosphere simulations corroborate the relationship between tropical Atlantic subsurface heat and salt storage driven by Salinity Maximum Water (SMW) and deglacial perturbations of the Atlantic Meridional Overturning Circulation (AMOC). Whether AMOC variability of the last glacial cycle affected SMW export into the tropical West Atlantic remained yet elusive. In order to assess the sensitivity of the tropical hydrography during abrupt and rapid glacial climatic and oceanic perturbations, we present century-resolving foraminifera-based subsurface (~200 m water depth) temperature and salinity reconstructions from Tobago Basin core M78/1-235-1. The proxy records were interpreted in terms of the closely related development of the North Brazil Current (NBC) and the North Atlantic Subtropical Gyre (STG) from ~37 to 30 ka BP, and in relation to their deglacial developments. Prior to ~32.8 ka BP, the cyclic variations in subsurface conditions were attributed to the NBC, which acted in line with a recurrent intensification and relaxation of the trade winds, subtle migrations of the Intertropical Convergence Zone, and the related moisture transport across Central America. Major and rapid re-organizations of the tropical Atlantic upper ocean-atmosphere system took place at ~32.8 ka BP and ~ 21.8 ka BP, unmirrored by major AMOC changes. Thresholds for sufficient heat and salinity accumulation in the STG to allow for formation and intensified subsurface dispersal of SMW were not achieved before late HS1, when AMOC weakening, according tropical heat backlog and surface warming by maximum Northern Hemisphere insolation acted together.